The second home owners handbook : - Haden, Jeff (Atlantic Pub. Group, 2006)
The Complete Guide to Second Homes for Vacations, Retirement, and Investment, Choosing the perfect location, Finding the right home, Forecasting investment potential, How to save thousands on financing, Here's the knowledge you need to find, buy, and get the most fun and profit from your second home,...